Green synthesis, characterization, and antibacterial activity investigation of zinc oxide nanoparticles using Rumex Nervosus Vahl Leaf extract - Tadesse Bizuayehu; Bidir Kassaw; Mihret Kendie (Results in Chemistry)
In this study, zinc oxide nanoparticles were synthesized using various ratios of the Rumex Nervosus Vahl Leaf extract and monohydrated zinc sulfate in solution. The phytochemical analysis of the leaf extract confirms the presence of alkaloids, phenolic, glycosides, tannins, saponins, and steroid-bioactive compounds. The synthesized zinc oxide nanoparticles were characterized by using UV–Vis, FT-IR, XRD, and TGA/DTA spectroscopic techniques. The average crystal size of the synthesized nanoparticles was found to be 43.44 nm, 69.82 nm, 84.8621 nm in 2:1, 1:2, and 1:1 ratios respectively. The in vitro antibacterial activities of the synthesized nanoparticles were tested on two Gram-positive (Bacillus, and S. aureus) and two Gram-negative (E. coli, and K. pneumonia) bacteria strains using the disc diffusion method. The antibacterial activities of zinc oxide nanoparticles showed comparable results with the antibiotic standards. Therefore, the eco- friendly synthesis of zinc oxide nanoparticles using Rumex Nervosus Vahl Leaf extract is a promising approach for developing new drug products with efficient antibacterial properties, and it could be evaluated as an opportunity for in vivo biomedical applications with positive environmental impacts.